Clinical and sensitization profile in peach allergy due to LTP sensitization - Gabriela, Zambrano Ibarra; M. Elena, Rodríguez Mazariego; Carlos, López Tovar; Marta, Blanco López; Ochoa M. Luisa, Baeza (Frontiers in Allergy, 2024)
BackgroundLipid transfer proteins (LTP) are associated with a wide range of severity of allergic reactions. However, the risk factors associated with this severity are not fully understood.ObjectivesTo describe the clinical characteristics of peach-allergic patients due to LTP sensitization and analyze the relationship between the severity of the reactions and patients’ sensitization profiles.MethodsA retrospective study of peach-allergic patients was performed. Patients were classified into LTP-monoallergic (only peach allergy) or LTP-Syndrome (peach allergy and allergy to other plants-foods related with LTP). Symptoms with Rosaceae family and other related plant foods, skin prick tests (SPTs), and IgE values were recorded.ResultsSeventy-one patients were included, 46.5% suffering from anaphylaxis, 32.3% from urticaria angioedema, and 21.2% from oral allergy syndrome. Six had monoallergy to LTP and 65 LTP syndrome. Clinical severity showed no differences according to peach SPT wheal size or Pru p 3 IgE levels. We also found no differences between the components of LTP-containing foods analyzed, the number of LTPs recognized, and the severity of symptoms. However, anaphylaxis was more frequent in patients with concomitant allergies to ≥3 groups of plant foods.ConclusionsLTP syndrome was the most common presentation in patients with Rosaceae food allergy. The severity of the reactions was not related to peach SPT wheal size or sIgE levels to Pru p 3, but concomitant allergies to ≥3 plant food groups could be a good marker of severity.